CHALLENGES TO MADE VALUES-BASED COMPETENCE MODEL FOR AMBULANCE PERSONNEL - Dambe, Gundega; Atstāja, Dzintra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The purpose of this paper is to clarify and analyse the understanding of the values for Ambulance personnel, to compare and integrate it with the system of competencies used in the performance assessment and evaluation of professional competence. The results of State Emergency Medical Service ambulance personnel’s survey in the 2018 are analysed in the research. The results obtained Ambulance personnel’s different understanding of the importance of organization's values and its impact in management, staff attitude and work performance. The results of the survey have showed that Ambulance personnel has contradictive understanding of system of values. Their personal values are respect, compassion, care, ethics, honesty, trust, however for their professional work they recognise teamwork, professionalism, safety, etc. as very important values.